HUBUNGAN STATUS GIZI DAN AKTIVITAS OLAHRAGA DENGAN TINGKAT KEBUGARAN JASMANI DI SMAN 6 PEKANBARU - Mutiara, Sherly; Anggarawati, Wiwik Suryandartiwi; Ilham, Faiz; Najla, Lisvia (Journal of Hospital Administration and Management (JHAM), 2023)
Physical fitness is an essential factor in supporting students' health and academic performance. Nutritional status and sports activity play a role in determining a person's level of physical fitness. This study aims to analyze the relationship between nutritional status and sports activity with the physical fitness level of students at SMAN 6 Pekanbaru. This study employs a cross-sectional design with a quantitative approach. The sample consists of students from SMAN 6 Pekanbaru selected using the purposive sampling method. Nutritional status was measured using Body Mass Index (BMI), sports activity was assessed through a physical activity questionnaire, and physical fitness was evaluated using the Indonesian Physical Fitness Test (TKJI). Data analysis was conducted using statistical correlation tests to determine the relationships between the study variables. The results showed a significant relationship between nutritional status and sports activity with students' physical fitness levels (p < 0.05). Students with normal nutritional status and higher sports activity levels exhibited better physical fitness compared to those who were less active or had non-ideal nutritional status. Therefore, maintaining a balanced diet and engaging in regular exercise is crucial for improving students' physical fitness.